EFFICACY OF CONSERVATIVE AND ORTHOPEDIC MEASURES IN THE TREATMENT OF AN INGROWN TOENAIL - A. G. Sonis; E. A. Stolyarov; D. G. Alekseev; I. V. Ishutov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
In this study, we analyzed the efficacy of the most common methods of conservative treatment and orthopedic correction of an ingrown toenail at early stages used in outpatient surgical practice. We evaluated treatment outcomes and compared them using the methods of evidence-based medicine. We found that the orthopedic approach is significantly more effective than conservative treatment.